Overview of ontology server research - Ahmad, Mohamad Nazir; Robert, M. Colomb (2007)
An ontology is increasingly becoming an essential tool for solving problems in many research areas. The ontology is a complex information object. It can contain millions of concepts in complex relationships. When we want to manage complex information objects, we generally turn to information systems technology. An information system intended to manage ontology is called an ontology server. The ontology server technology is at the time of writing quite immature. Therefore, this paper reviews and compares the main ontology servers that have been reported in the literatures. As a result, we point out several research questions related to server technology.